Effects of pH, temperature and shear on the structure–property relationship of lamellar hydrogels from microbial glucolipids probed by in situ rheo-SAXS. Issue 10 (25th February 2020) - Ben Messaoud, Ghazi; Le Griel, Patrick; Hermida-Merino, Daniel; Baccile, Niki
Abstract : The structure-properties relationship of lipid lamellar hydrogels composed of a biobased microbial glucolipid biosurfactant is studied against pH, temperature and shear rate using in situ rheo-SAXS experiments. Abstract : Lipid lamellar hydrogels are a class of soft materials composed of a defectuous lipid lamellar phase, where defects are classically stabilized by polymer or surfactant inclusions in lipid membranes. We have recently shown that bolaform microbial glucolipids, composed of a single glucose headgroup and a C18:0 fatty acid, with the carboxylic acid group located opposite to glucose, spontaneously form lamellar hydrogels at room temperature below pH 8. In this work, we combine rheology with small angle X-ray scattering (SAXS), rheo-SAXS, to correlate, in situ, the structural and mechanical properties of microbial glycolipid lamellar hydrogels upon application of three different stimuli: pH, temperature and a shear rate. In all cases we find unusual structural features of the lamellar phase if compared to classical phospholipid lamellar structures: reducing pH from alkaline to acidic induces a sol-to-gel transition during which an increasing elastic modulus is associated with an oscillatory evolution of lamellar d (100) spacing; temperature above T m and increasing shear induce the formation of spherulitic crumpled domains, instead of a classically-expected lamellar-to-vesicle or lamellar-to-onion phase transitions.